2019
DOI: 10.1186/s40561-019-0097-y
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing patterns of student’s modeling behaviour patterns via process mining

Abstract: Evaluating student learning effect plays an essential role in education, which is typically done by assessing student's final deliverables. However, the student's learning process has not been properly explored in the past. In this paper, we propose an interactive student learning effect evaluation framework which focuses on in-process learning effect evaluation. In particular, our proposal analyzes students modeling assignment based on their operation records by using techniques of frequent sequential pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Furthermore, the dynamicity and elegance of learning processes in social networks can enhance several advantageous qualities. As Wang et al ( 2019 ) discovered, modeling student behaviors are an essential factor that facilitates learning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the dynamicity and elegance of learning processes in social networks can enhance several advantageous qualities. As Wang et al ( 2019 ) discovered, modeling student behaviors are an essential factor that facilitates learning.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of studies (Wang and Wu 2008 ) conducted in different environments with various research methodologies suggested that students who receive effective, timely feedback in e-learning environments exhibit better and higher-quality performance in e-learning. These studies showed the importance of providing a framework to assess student learning impact by emphasizing assessment during the learning process (Wang et al 2019 ). The literature on e-learning environments points to the need for further systematization requires the development of models for designing several constructs, such as user-centered design, educational diversity, blended learning spaces, and facilitating mixed or blended learning (Freigang et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bogarín et al [35] based on data from LMS logs managed to obtain more specific and accurate models of students' bahaviour. The online modeling platform BJUTModeling was used in studies [36] and [37] as a tool for student learning evaluation effect. Based on PM, authors achieved student modeling patterns mining and their behaviors interpretation.…”
Section: Lms Lad and Online Coursesmentioning
confidence: 99%